Public expenditures, educational outcomes and grade inflation: Theory and evidence from a policy intervention in the Netherlands - Kristof De Witte; Benny Geys; Catharina Solondz (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Previous work on the relation between school inputs and students' educational attainment typically fails to account for the fact that schools can adjust their grading structure, even though such actions are likely to affect students' incentives. Our theoretical model shows that, depending on schools' and students' reactions to resource changes, the overall effect of spending on education outcomes is ambiguous. Schools, however, adjust their grading structure following resource shifts, such that grade inflation is likely to accompany resource-driven policies. Exploiting a quasi-experimental policy intervention in the Netherlands (where the grading system relies on both standardized central and schoollevel exams), we find that additional resources benefit educational attainment only when they are substantial, but induce grade inflation otherwise.
Keywords: I20; I28; H52; 330; public expenditures; grade inflation; educational attainment; standardized central exam